First isolation of Leptospira interrogans from the arboreal squirrel Callosciurus erythraeus introduced in Argentina - Gozzi, Ana Cecilia; Guichon, Maria Laura; Benitez, Verónica Victoria; Romero, Graciela Noemi; Auteri, Carmelo Domingo; Brihuega, Bibiana Felicitas (Bioone, 2019)
We isolated Leptospira strains from renal tissue samples of Asiatic red-bellied squirrels Callosciurus erythraeus, captured in Argentina. In December 2008, we captured 34 squirrels in the province of Santa Fe during a short control campaign, which were screened for Leptospira spp. by direct immunofluorescence assays and isolation attempts in renal tissue samples. A prevalence of 38% of Leptospira spp. was obtained by direct immunofluorescence. The isolates, genotyped by the MLVA, were identified as L. interrogans Canicola (N = 2) and L. interrogans Icterohaemorraghiae (N = 1), showing an identical genetic profile to the reference strains Hond Utrech IV (serovar Canicola, serogroup Canicola) and M20 (serovar Copenhageni, serogroup Icterohaemorrhagiae), respectively. Our study shows for the first time that the red-bellied squirrel is a renal carrier of Leptospira interrogans and might act as a reservoir of leptospirosis both in native range and areas of introduction within several European countries, Japan and Argentina. The close association of this introduced squirrel species with humans and domestic animals may increase the probability of disease transmission, particularly in favourable environments.